Somalia as a failed state: Internal and external dynamics / Hassan Sheikh Ali Nur - Hassan , Sheikh Ali Nur (2016)
This study is "Somalia As A Failed State: Internal and External Dynamics", and examines both the internal and external factors that have contributed to the failure of Somalia. The aim is to examine how the internal factors contributed to the failure of Somalia; similarly, how have external factors contributed to the failure of Somalia? This is to start with a short introduction of Somalia historical background, problem statement, major research questions and objectives, literature review, research methodology, and limitations. Internally, the research will study who the Somalis are, Europeans early contacts with Somalis, the Europeans divide-and-control policy, Somalis response to the colonialists, the Jihadist Movement (1900-1920), the Nationalist Movement (1940-1960), and the United Nations Trusteeship's effects on Somalia. Moreover, the study will cover the weakness of civilian rule in Somalia (1960-1969) and military misrule (1969-1991). Externally, the study will highlight the major factors that attracted global powers to come to Somalia, the impact of the Cold Warï¿½s politics on Somalia, particularly the Soviets and the United States roles in Somalia's politics (1963-1977 and 1980-1991). Also, the study will highlight the impact of the Horn of Africa's rivalry, particularly between Somalia and Ethiopia. Finally, the study also summarizes the research findings that include internal leadership failure, clan politics in Somalia, the impact of Europeans divide-and-rule policies during the colonial period, aid dependency and economic mismanagement. Externally, the research identifies Somalia as a chessboard of global powers and the impact of the region's rivalry.